2017
DOI: 10.1166/jnn.2017.13335
|View full text |Cite
|
Sign up to set email alerts
|

RGD Conjugated Dendritic Polylysine for Cellular Delivery of Antisense Oligonucleotide

Abstract: Dendritic polylysines (DPL) are highly branched nano-sized spherical polymer with positively charged primary amino groups on surface. This structural feature is useful for a delivery of antisense oligonucleotide or siRNA. In this study, we modified the surface of DPL with cyclic RGD (and iRGD) peptide by conjugation reaction generating RGD (and iRGD) peptide conjugated dendritic poly-lysines, RGD-DPL or iRGD-DPL. The prepared conjugates were evaluated for integrin receptor-mediated cellular delivery of antisen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To improve cellular uptake, asONs are conjugated with various delivery-promoting molecules, including cholesterol [ 36 ], polyethylene glycol [ 37 , 38 ], α-tocopherol [ 39 , 40 ], cell-penetrating peptides [ 41 , 42 ], etc. Despite the perspective of this approach, the redundant modifications of asONs with such molecules, especially in combination with modifications of the oligonucleotide backbone to improve their nuclease resistance, can significantly affect their biological activity, create problems in adaptation of length and composition of linker groups and, finally, complicate the scheme of asON synthesis and isolation as well as increase their cost.…”
Section: Introductionmentioning
confidence: 99%
“…To improve cellular uptake, asONs are conjugated with various delivery-promoting molecules, including cholesterol [ 36 ], polyethylene glycol [ 37 , 38 ], α-tocopherol [ 39 , 40 ], cell-penetrating peptides [ 41 , 42 ], etc. Despite the perspective of this approach, the redundant modifications of asONs with such molecules, especially in combination with modifications of the oligonucleotide backbone to improve their nuclease resistance, can significantly affect their biological activity, create problems in adaptation of length and composition of linker groups and, finally, complicate the scheme of asON synthesis and isolation as well as increase their cost.…”
Section: Introductionmentioning
confidence: 99%
“…The results were attributed to the specific binding ability of iRGD to integrin receptors αvβ3 and αvβ5 overexpressed in tumour cells [ 30 , 31 ]. Upon cleavage by proteases, the C-terminal rule (C and R) motif is exposed and consequently binds to the neurexin-1 (NRP-1) receptor; the cleaved form of iRGD binds to NRP-1 and subsequently triggers NRP-1-dependent endocytosis, thereby enhancing tumour penetration [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of the RGD peptide depends on the backbone conformation, the charged side chains of the Arg and Asp residues, and the hydrophobic moieties of the flanks of Asp residues (Schaffner and Dard 2003). The RGD motif's freedom of conformation determines its binding strength to the integrin, and molecular dynamics simulations have shown that while RGD motifs are mostly exposed to solvents that can be bound in all synthetic systems, their flexibility depends on the refined geometry (Le et al 2017). The interaction between the RGD peptides and integrin αVβ3 is influenced by direction and distance (Dong et al 2017).…”
Section: Structure Of Rgdmentioning
confidence: 99%